Model of Increasing Tourist Satisfaction through Attraction, Accessibility, Security, Safety, Health and Hygiene at the Ujung Kulon National Park - Soehardi, Soehardi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this research was to analyze the model of increasing tourist satisfaction through attraction, accessibility, safety and security, health and hygiene in Ujung Kulon National Park, Pandeglang Regency, Banten Province. The population in this research were all foreign and domestic tourists who visited Ujung Kulon National Park with the sample used was purposive sampling totaling 95 respondents. Quantitative research methods are used in this study with analysis of construct validity and reliability, outer loading, collinearity statistics, path coefficients, R square and model fit. The result of this research is that there is a significant effect of attraction on tourist satisfaction, accessibility on tourist satisfaction, security and safety on tourist satisfaction and health and hygiene on tourist satisfaction in Ujung Kulon National Park. It can be concluded that tourist satisfaction is influenced by attraction, accessibility, safety and security and health and hygiene in Ujung Kulon National Park.